Safety management systems for aviation : a practical guide - Australia. Civil Aviation Safety Authority (Canberra, ACT : Civil Aviation Safety Authority, 2014)
The CD and DVD are part of the SMS for aviation: a practical guide resource kit for organisations which are in the process of implementing , or about to implement, a safety management system in their business. On the DVD are two dramas: SOS and SMS, which feature a fictitious charter and training organisation. The DVD also showcases a wide range of industry subject matter experts in a series of interviews, "What the experts say". The CD contains copies of the eight resource kit booklets, further reading, and a set of templates to assist in SMS documentation.
Title from disc labels.
System requirements
Keywords: Airlines -- Risk management; Airlines -- Safety measures; Aeronautics -- Safety measures; Australian